KEPENTINGAN RUSIA DALAM KERJASAMA GAS ALAM DENGAN TIONGKOK - Ilham Syakbanur Rahamt; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study discusses Russian interests in the natural gas sector collaborating with China. EU provides economic sanctions against Russia after the conflict between Russia - Ukraine in 2009 and the annexation of the Crimea in the year 2014 made Russia is not allowed to export natural gas as main commodity as main income countries to the European Union as main consumer. Russia, which has abundant natural gas reserves, certainly needs a new market share of natural gas so that the excess natural gas reserves can be used as state revenues. Through the Eastern Gas Program project in 2014, Russia appointed China as the main market base for the sale of natural gas. This collaboration provides economic and political benefits to Russia. In international cooperation, countries that are interconnected together take an approach to find solutions to problems faced through approaching eachother. Through the Eastern Gas Program, Russia exploit China who are unable to meet the natural gas needs for the development of state-owned industries as a result of rapid growth. The Eastern Gas Project This program is a collaborative program created by Russian-owned energy company Gazprom agreed upon by China's energy company China National Petroleum Corporation. Which is where the agreement Russia will send natural gas to meet China's industrial needs. Keywords: Interest, Natural Gas, Eastern Gas Program, Russia, China